Pengadaan Social Media Inteligence System Menggunakan Metode TOPSIS: Procurement of Social Media Intelligence System Using TOPSIS Method - Haveiszal Faroqie; Monica Mey Jesika Rani; Risky Wicaksono, Soetam (Universitas Bojonegoro, 2024)
Social media intelligence systems are becoming an important source of data for organizations and enterprises, providing insights into public behavior, preferences, and opinions. They help monitor issues, detect potential threats, and support data-driven decision-making. A key challenge was the procurement of suitable hardware, involving collaboration between IT teams, management, and stakeholders. The TOPSIS method was used to determine the hardware that best suited the organization's needs and budget, optimizing system performance. Analysis was conducted on three enclosure alternatives considering storage, connection, PSU, warranty, and price, with the greatest weight on storage and connection. The results showed the DELL PowerEdge MX7000 Enclosure as the highest scoring option, although it did not excel in some parameters. The application of this method optimizes IT investments and supports the implementation of an effective social media intelligence system, according to the needs and budget of the organization. Proper hardware procurement avoids financial losses and ensures optimal system functioning.